Triumphant evocations: The visualization and textualization of post-bop jazz in the 1950s - İnce, Ezgi. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
Jazz, since its early conception has always played a definitive role in American arts and culture. In the tumultuous post-war era of the 1950s that simultaneously cherished mass consumption, the avant-garde turn jazz took resonated with the influences of minorities that fell outside the racial, social and economical norms of American society. Visual and literary artists were influenced by the unusual rhythms and spontaneous virtuosity of jazz musicians and began to emulate them in their respective genres. Jazz, as an abstract music form, defied accurate verbal or visual illustration, however. This thesis argues, that what is inherently an abstracted language in modern jazz achieved representation both through the intermedial experiments of the Abstract Expressionist visuals on album covers and some schools of poetry in the 1950s. The thesis examines album covers of post-bop jazz and determines its main audience, while simultaneously studying patterns of modern jazz in the poetry of Bob Kaufman, Frank O’Hara and Langston Hughes within the context of the “new listener”.
Keywords: Jazz -- 1951-1960 -- History and criticism.